DIRECTION OF IMPROVEMENT OF ROAD DATA COLLECTING VEHICLES - Smolyanyuk, Roman; Smolyanyuk, Nadiya (Sworld-Us Conference proceedings, 2023)
The main means of obtaining up-to-date information on the condition of highways remain road data collecting vehicles. An integral element of such systems are means of video diagnostics of highways. The modern level of computer technology allows you to ope